Mastocytosis in plaques with secondary pachyderma. - Garofalo, L. (European Journal of Pediatric Dermatology, 2023)
Cutaneous mastocytosis is a clonal proliferation of mast cells that in children usually begins in the first months of life, does not affect other organs and tends to regress spontaneously. An exceptional case of cutaneous mastocytosis is presented which began at 5 months with about ten plaques; on the latter recurring bullous lesions arose; later the urtication and blister episodes progressively diminished, but at the age of 13 the plaques were still present with pachydermic skin and dilated and depressed follicular ostia.